Broadband Direct UVA irradiance measurement for clear skies evaluated using a smartphone. Issue 4 (1st December 2014) - Igoe, D.; Parisi, A. V.
Abstract: UVA wavelengths (320–400 nm) have been implicated in recent studies to contribute to melanoma induction and skin photoaging in humans and damage to plants. The use of smartphones in UVA observations is a way to supplement measurements made by traditional radiometric and spectroradiometric technology. Although the smartphone image sensor is not capable of determining broadband UVA irradiances, these can be reconstructed from narrowband irradiances, which the smartphone, with narrowband and neutral density filters, can quantify with discrepancies not exceeding 5 %. Three models that reconstruct direct broadband clear sky UVA were developed from narrowband irradiances derived from smartphone image sensor pixel data with coefficients of determination of between 0.97 and 0.99. Reasonable accuracy and precision in determining the direct broadband UVA was maintained for observations made with solar zenith angles as high as 70°. The developed method has the potential to increase the uptake of the measurement of broadband UVA irradiances.